Avaliação da resistência ao desgaste abrasivo de diferentes resinas compostas antes do polimento, após o polimento e após a escovação simulada - Rosa, Rochana Gomes (2011)
The aim of this in vitro study was to evaluate the wear strength of four resin composites Filtek Supreme (3M ESPE) Esthet X (Denstply), Durafill VS (Heraeus Kulzer) e Opallis (FGM). Ten cylinder-shaped specimens (8mm diameter, 3mm thickness) of composite resin (A2 shade) were made for each material. Wear strengths were evaluated by mass and surface roughness changes of the specimens subjected to polishing and simulated brushing. Baseline (no polishing), median (after polishing) and final (after simulated toothbrushing) measurements were obtained using a precision electronic balance with 0.0001g (10-4) accuracy. Baseline, median and final surface roughness measurements were made using a profilometer Surtronic 3+ (Taylor-Hobson), Ra parameter in µm, cut-off 0.25mm and 2,5mm traversing length. Abrasion test was performed in a toothbrushing simulation device, using soft bristle toothbrushes, 200g loading, 374 cycles/min and a dentifrice/deionized water slurry in a 1:2 proportion. The specimens were subjected to 100.000 brushing cycles. The toothbrushes were replaced each 50,000 cycles and the slurry was continuously replaced throughtout the test. Mass loss changes and surface roughness were calculated from the differences between baseline and median, median and final mass mean values, and were then converted in percent. Data were statistically analyzed using paired t-Test, Wilcoxon, Kruska-Wallis, Mann-Whitney, and Pearson correlation tests (p<0,05). The results have shown that all the material presented statistically significant mass loss, and a significant increase of surface roughness after the simulated toothbrushing. Regarding the mass changes, the wear strengths of the material, after polishing, in the increasing order were (FS=DU) > (OP=EX), and after simulated toothbrushing were ((FS=DU) > (OP=DU=EX). The surface roughness after polishing in increasing order of the material were (FS=OP)<(OP=EX=DU), and after simulated toothbrushing were (FS=OP=EX=DU). The methods of wear strength evaluation did not present correlation. It was concluded that the resins composites 10 tested presented statistically significant differences of wear strengths. However, all composites presented wear and increased surface roughness because of the abrasive forces from simulated toothbrushing. Mass loss and surface roughness changes did not present statistic correlation.